Development of vocabulary card in learning english vocabulary for 7th grade students at MTs Ma’arif Gandusari - Yogi Dayana Buana Maharani; Siti Rofi’ah; Ahmad Saifudin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2023)
English has an important role in the international world. Vocabulary is the key of the four English skills. Need mastery the vocabulary to facilitate the delivery of the material. This research was conducted to develop subject matter in the form of vocabulary cards as learning media in class VII. The object of this research is 24 students of MTs Ma'arif NU Gandusari for the academic year 2020/2021. This research is a research and development model by (Borg & Gall : 2003) modified by researcher based on the needs and context of the research. There are eight steps in this development: (1) conducting needs analysis, (2) determine the specific material, (3) product design, (4) design validation, (5) design revision, (6) product testing, (7) usage testing, (8) dissemination and implementation. Questionnaire was applied to get the data. The results of media expert validation showed that the illustration got a score of 83% and the student response was 95%. The results of the validation of the material, media, and student responses can be said that this Vocabulary card has a “valid” level of validity to be used. Therefore, this learning media deserves to be an effective learning media for students.